To find the solution of the equation 5/3 - 2x = 1/6, we can start by isolating the variable.
First, we can subtract 5/3 from both sides to eliminate the fraction:
-2x = 1/6 - 5/3
To combine the fractions on the right side, we need to find a common denominator. The common denominator for 6 and 3 is 6:
-2x = 1/6 - 10/6
Now, we can subtract the fractions:
-2x = (1 - 10)/6
Simplifying:
-2x = -9/6
Next, we can simplify the fraction:
-2x = -3/2
Finally, we can solve for x by dividing both sides by -2:
x = (-3/2) / -2
Dividing a fraction by a fraction is the same as multiplying by the reciprocal. In this case, the reciprocal of -2 is -1/2:
x = (-3/2) * (-1/2)
Multiplying the fractions gives:
x = 3/4
Therefore, the solution to the equation 5/3 - 2x = 1/6 is x = 3/4.
What is the solution of the equation 5/3−2x=1/6 ?(1 point)
Responses
3
3
−11/3
negative Start Fraction 11 over 3 End Fraction
−11/12
negative Start Fraction 11 over 12 End Fraction
3/4
1 answer